ANALYSIS OF THE FINANCIAL CONDITION OF JSC "UZBEKISTAN TEMIR YULLARI" (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The purpose of this article is to analyze the financial condition and financial results of JSC "Uzbekistan Temir Yullari" in accordance with the accounting standards. Abstract: The purpose of this article is to analyze the financial condition and financial results of Uzbekistan Temir Yullari JSC in accordance with the standards of financial reporting.